Report of the Study Team on Prohibition - Planning Commission (Planning Commission, 1963)
The Study Team on Prohibition was appointed by the Planning Commission vide their Resolution No. 16(5)/63-Pub., dated the 29th April, 1963. the Resolution appointing the Study Team also indicated the purpose of the Study and its scope as follows ; “The Government of India recently reviewed the position in consultation with the State Governments and decided that the working of the Prohibition programme should be studied for the country as a whole. Such a study will cover problems connected with the enforcement of Prohibition and Excise Laws, measures intended to reduce illicit traffic in liquor, improving administrative efficiency and securing to the maximum extent public support for the programme through the co-operation of both official and non-official agencies”.
Report of the Study Team on Prohibition
Government of India